2010
DOI: 10.11120/msor.2010.10020031
|View full text |Cite
|
Sign up to set email alerts
|

Coursework, what should be its nature and assessment weight?

Abstract: Opinions differ about the nature, frequency and relative assessment weight of coursework in a mathematics degree. Short frequent coursework may aid week by week engagement while a smaller number of longer tasks may be better linked to real applications and give more opportunity for open ended questions. What should be the mix between assessment types? To what extent is copying a problem and how should this be balanced against the opportunity coursework can afford for investigation and originality? Given the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, students' contribution to class activities should be encouraged with more opportunities for students to participate offered by instructors (Hard & RaoShah, 2021). Frequent small tasks promote engagement and can help students keep up with the material delivered (Thomlinson et al, 2010). Studies have shown that intense weekly participation grading schemes can increase participation and overall course grades (Tang et al, 2020).…”
Section: Literature Review and Hypothesis Development 21 Class Partic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, students' contribution to class activities should be encouraged with more opportunities for students to participate offered by instructors (Hard & RaoShah, 2021). Frequent small tasks promote engagement and can help students keep up with the material delivered (Thomlinson et al, 2010). Studies have shown that intense weekly participation grading schemes can increase participation and overall course grades (Tang et al, 2020).…”
Section: Literature Review and Hypothesis Development 21 Class Partic...mentioning
confidence: 99%
“…The classic conception of class participation, limited to verbal interactions, has been overtaken by a much broader view, including anything that causes students to be more involved in active learning forms (Orwat et al, 2017). Class participation is a multidimensional concept that comprises many aspects that suggest evidence of student engagement, such as preparation prior to class (Dancer & Kamvounias, 2005;Hard & RaoShah, 2021), attendance (Dancer & Kamvounias, 2005;Fritschner, 2000;Hard & RaoShah, 2021), contribution to class activities and discussions (Dallimore et al, 2010;Dancer & Kamvounias, 2005;Fritschner, 2000;Xu & Qiu, 2020) and frequent small tasks (Tang et al, 2020;Thomlinson et al, 2010). Past research shows that these activities lead to personal and professional growth in students (Jones, 2008), result in a better understanding and retention of the material (Precourt & Gainor, 2019), enable students to demonstrate a broader range of skills (Richardson, 2015) and improve students' performance (Papageorgiou, 2019;Paisey & Paisey, 2004;Precourt & Gainor, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic conception of class participation, which is limited to verbal interactions, has been overtaken by a much broader view, including anything that causes students to be more involved in active learning forms (Orwat et al, 2018). Class participation is a multidimensional concept that comprises many aspects that suggest evidence of student engagement, such as preparation prior to class (Dancer & Kamvounias, 2005; Hard & RaoShah, 2022), attendance (Dancer & Kamvounias, 2005; Fritschner, 2000; Hard & RaoShah, 2022), contribution to class activities and discussions (Dallimore et al, 2010; Dancer & Kamvounias, 2005; Fritschner, 2000; Xu & Qiu, 2022) and frequent small tasks (Challis et al, 2010; Tang et al, 2020). Past research shows that these activities lead to personal and professional growth in students (Jones, 2008), result in a better understanding and retention of the material (Precourt & Gainor, 2019), enable students to demonstrate a broader range of skills (Richardson, 2015) and improve students’ performance (Paisey & Paisey, 2004; Papageorgiou, 2019; Precourt & Gainor, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although students demand timely (Marriott & Lau, 2008), constant and regular feedback (Watty et al, 2013), they usually complain about receiving grades too late or even never receiving them, which does not allow them to make corrections. The lack of frequent feedback concerns students, especially regarding class participation (Bouilheres, 2015; Rowe & Wood, 2009), and requires consideration since prompt feedback could enhance students’ weekly engagement (Challis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%